PERCEPTIONS ON SOCIAL COMPETENCE BIOLOGY TEACHER CANDIDATES - Bunga, Yohanes Nong; Azri, Harizqi; Sharma, Tushar (Universitas PGRI Sumatera Barat, 2021)
This study aimed to analyze the perception of the social competence for biology teacher candidates. This study uses a qualitative method with a descriptive approach. Research subjects were determined by using purpose sampling technique. Data were collected through interviews, filling out questionnaires, and document studies. The validity of the data was determined using source triangulation and technical triangulation. Data analysis techniques are carried out by means of data reduction, data display, and conclusion or verification. The results showed that the perception on the social competence of biology teacher candidates was in the good category. This research can be used as a basis for conducting research related to teacher competence in the future.